Decriminalizing domestic violence: a balanced policy approach to intimate partner violence - Goodmark, Leigh (Gender and justice, 2018)
"Decriminalizing Domestic Violence asks the crucial, yet often ignored, question of why and how the criminal legal system has become the primary response to intimate partner violence in the United States. It introduces readers, both new and well versed in the subject, to the ways in which the criminal justice system harms rather than helps those who are subjected to abuse and violence in their homes and communities. The book examines how mandatory arrests, no-drop prosecutions, zero-tolerance public housing policies, and the ever-growing collateral consequences of a criminal record can mean that vast amounts of social, legal, and financial resources are diverted into a criminal justice apparatus that is ultimately unable to deliver justice or safety to victims, or to prevent domestic violence to begin with. Envisioned for both courses and research topics in domestic violence, family violence, gender and law, sociology of law, and others, the book challenges readers to view intimate partner violence not as a criminal justice concern but as an economic, public health, community, and human rights problem. At a moment when we are examining our national addiction to punishment, Decriminalizing Domestic Violence offers a thoughtful, pragmatic roadmap to real domestic violence reform"--Provided by publisher